1981
DOI: 10.1007/bf00119925
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of aircraft measurements of momentum flux in the subcloud layer over the tropical atlantic ocean during gate

Abstract: The momentum flux data obtained by the gust probe aboard the NOAA DC-6 aircraft during GATE are analyzed. Vertical profiles are obtained for Phases I and III and correlated with vertical wind velocity profiles using the geostrophic departure method. Reasonable agreement is obtained using the horizontal equations of motion with negligible advective acceleration. The vertical profiles of momentum flux and wind speed variance compare well with the numerical model results of Deardorff (1972) and Wyngaard et al. (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

1981
1981
1991
1991

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 27 publications
2
6
0
Order By: Relevance
“…Substituting this into (15) and taking the ratio CD(10)/C,(50) results in a factor 1.23, and a profile-derived drag coefficient of C&10) = 1.55 x 1o-3 which is somewhat lower than the velocity band derivation of the drag coefficients in the previous section but is in agreement with drag coefficients from GATE gust probe data (Greenhut, 1981).…”
Section: Vertical Flux Profilessupporting
confidence: 73%
See 2 more Smart Citations
“…Substituting this into (15) and taking the ratio CD(10)/C,(50) results in a factor 1.23, and a profile-derived drag coefficient of C&10) = 1.55 x 1o-3 which is somewhat lower than the velocity band derivation of the drag coefficients in the previous section but is in agreement with drag coefficients from GATE gust probe data (Greenhut, 1981).…”
Section: Vertical Flux Profilessupporting
confidence: 73%
“…GATE values range from 0.03 to 0.09 N me2 (Greenhut, 1981). The wind speeds during GATE were correspondingly lower, with a typical value of 5 m s-i, whereas the profile in Figure 6 gives a value of 8.5 m s-l at 50 m. Using (12), the calculated drag coefficient at 50 m from the vertical profiles is CD(50) = 1.26 x 1O-3 .…”
Section: Vertical Flux Profilesmentioning
confidence: 96%
See 1 more Smart Citation
“…Previous studies (Wipperman, 1972;Clarke and Hess, 1974;Brook and Allen, 1978) have shown that the similarity functions A, B, C, and D are relatively insensitive to thermal wind shear effects which, in any case, are small in the tropics (Greenhut, 1981).…”
Section: Parameterization Schemementioning
confidence: 89%
“…Meteorological conditions during the NORPAX flights are described by Ramage et al (1979;1981). The near-tropical convergence zone (CZ) was always south of 11' N and north of the equator so that the ascents and descents at 11' N were north of the CZ and those at or near the equator were south of the CZ in all cases.…”
Section: Data Source and Interpretationmentioning
confidence: 99%